SISTEM PAKAR DIAGNOSA GANGGUAN MESIN EDC MENGGUNAKAN METODE FORWARD CHAINING PADA BANK INDONESIA - Fernaldo, Aggasy Problema; Sani, Asrul (STMIK Widuri Jakarta, 2023)
An EDC (Electronic Data Capture) machine is an electronic device used to collect, store and manage electronic payment transaction data, such as credit or debit cards. Typically, EDC machines are used by merchants or retailers to accept payments from customers by credit or debit card. EDC machines connect to electronic payment networks and facilitate secure data transfer between customer cards and payment systems. The aim is to implement the forward chaining method and create an expert system that can diagnose EDC machine damage and disturbances. The forward chaining method is used in this research. The result is that the forward chaining method can be implemented in an expert system and the system can be used to diagnose damage and disturbances to EDC machines.